The combination of different nitrogen fertilizer types could promote rice growth by alleviating the inhibition of straw decomposition. (4th June 2021) - Tang, Jichao; Zhang, Ruoyu; Li, Hechao; Tan, Jiali; Song, Wenjie; Wen, Xin; Lu, Bilin; Hu, Zhengrong
Abstract: Straw return plays an important role in the improvement of farmland ecological environments, increasing soil fertility, crop quality, and yield. However, in the early growth of rice ( Oryza sativa L.), straw decomposition and rice growth may be inhibited by suboptimal carbon/nitrogen (C/N) ratios. We, therefore, explored methods that could alleviate the inhibition of straw decomposition using different combinations of ammonium bicarbonate and compound fertilizer. No fertilizer (CK) and compound fertilizer (S0) were used as the control. The ratios of added ammonium bicarbonate were 10% (S1), 20% (S2), 30% (S3), and 40% (S4), respectively. Compared with the S0 treatment, the S2 treatment accelerated straw decomposition, promoted the early growth of tillers and roots, and improved the leaf area index, dry matter accumulation, and N use efficiency (apparent N utilization, agronomic N utilization, and partial factor productivity increased by 4.05‒19.48% in two years). Moreover, panicle number, filled‐grain percentage, and 1000‐grain weight were significantly higher in the S2 treatment than other treatments. The grain yield of S2 treatment was significantly higher than that of S0 treatment by 4.06% (2019) and 5.66% (2020). Regression analysis revealed that the optimal ratios of ammonium bicarbonate for increasing straw decomposition and grain yield were relatively close, 16.27% and 14.60%, respectively. These results suggest that compared with conventional fertilization method (S0), the 20% treatment is a more effective fertilization method that prevents inhibition of straw decomposition, promoting rice growth and yield, and improving nitrogen (N) use efficiency. Abstract : Ammonium bicarbonate combined with compound fertilizer in base fertilizer were used to investigate their effect on straw degradation and rice growth.